Dynamic optimization of trajectory for ramp‐up current profile in tokamak plasma1. Issue 6 (26th August 2016) - Ren, Zhigang; Xu, Chao; Ou, Yongsheng
Abstract: In this paper, we consider an open‐loop, finite‐time, optimal control problem of attaining a specific desired current profile during the ramp‐up phase by finding the best open‐loop actuator input trajectories. Average density, total power, and plasma current are used as control actuators to manipulate the profile shape in tokamak plasmas. Based on the control parameterization method, we propose a numerical solution procedure directly to solve the original partial differential equation (PDE)‐constrained optimization problem using gradient‐based optimization techniques such as sequential quadratic programming. This paper is aimed at proposing an effective framework for the solution of PDE‐constrained optimization problem in tokamak plasmas. A more user‐friendly and efficient graphical user interface is designed in MATLAB, and the numerical simulation results are verified to demonstrate its applicability. In addition, the proposed framework of combining existing PDE and numerical optimization solvers to solve PDE‐constrained optimization problem has the prospective to target challenge advanced control problems arising in more general chemical engineering processes. © 2016 Curtin University of Technology and John Wiley & Sons, Ltd.